2016
DOI: 10.1186/s11671-016-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Petroleum Coke-Derived Carbon for Synergistically Enhanced Capacitive Performance

Abstract: Petroleum coke is a valuable and potential source for clean energy storage if it could be modified legitimately and facilely. In the present study, porous carbon with high surface area and abundant oxygen-containing groups was prepared from petroleum coke by chemical activation and modification processes. The as-prepared carbon exhibits a high surface area (1129 m2 · g−1) and stable micrographic structure. It presents a high specific capacitance and excellent rate performance in KOH electrolyte. Even at an ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The specific capacitance of precursors, 0.3 KOH, 0.5 KOH, 0.7 KOH, 0.9 KOH, 0.3 ZnCl 2 , 0.5 ZnCl 2 , and 0.7 ZnCl 2 , was investigated using CV at a scanning rate of 1 mV s −1 (Figure 7). Simultaneously, the capacitive properties were measured in an aqueous electrolyte for KOH/ZnCl 2 treatment of PJs electrode observed the quasi‐rectangular shaped CV curve by showing the normal typical double‐layer capacitance of carbon materials 50,51 . These treatments facilitated the increase in specific capacitance, resulting from the activation process ability to significantly elevate the SSA, hierarchical porous nanofiber with abundant micro‐ and mesopores.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The specific capacitance of precursors, 0.3 KOH, 0.5 KOH, 0.7 KOH, 0.9 KOH, 0.3 ZnCl 2 , 0.5 ZnCl 2 , and 0.7 ZnCl 2 , was investigated using CV at a scanning rate of 1 mV s −1 (Figure 7). Simultaneously, the capacitive properties were measured in an aqueous electrolyte for KOH/ZnCl 2 treatment of PJs electrode observed the quasi‐rectangular shaped CV curve by showing the normal typical double‐layer capacitance of carbon materials 50,51 . These treatments facilitated the increase in specific capacitance, resulting from the activation process ability to significantly elevate the SSA, hierarchical porous nanofiber with abundant micro‐ and mesopores.…”
Section: Resultsmentioning
confidence: 92%
“…Simultaneously, the capacitive properties were measured in an aqueous electrolyte for KOH/ZnCl 2 treatment of PJs electrode observed the quasi-rectangular shaped CV curve by showing the normal typical double-layer capacitance of carbon materials. 50,51 These treatments facilitated the increase in specific capacitance, resulting from the activation process ability to significantly elevate the SSA, hierarchical porous nanofiber with abundant micro-and mesopores. Conversely, the precursor samples showed a relatively small quasi-rectangular shape, which indicates a lesser specific capacitance of 38 F g À1 .…”
Section: Electrochemical Performancesmentioning
confidence: 99%
“…The C1s spectra ( Figure 4E) can be deconvoluted into five individual components that are assigned to C─C/C─H (284.4 eV), C─O (285.6 eV), C═O (286.6 eV), O─C═O (288.6 eV), and π→π * (290.6 eV). 45 In addition, π→π * bond suggests the presence of the conjugated systems, which is favorable to improve the conductivity of PCs. 45 In addition, π→π * bond suggests the presence of the conjugated systems, which is favorable to improve the conductivity of PCs.…”
Section: Physicochemical Properties Of Pcsmentioning
confidence: 99%
“…42,43 It was generally accepted that O─C═O can improve the surface wettability of PCs 44 and C═O can be used as active sites to provide additional pseudocapacitance through Faradic reactions. 45 In addition, π→π * bond suggests the presence of the conjugated systems, which is favorable to improve the conductivity of PCs. 46 The deconvoluted N1s spectra ( Figure 4F) showed four individual peaks, attributing to pyridinic-N (398.8 eV), pyrrolic-N (400.2 eV), quaternary-N (401.3 eV), and pyridine-N-oxide (402.6 eV).…”
Section: Physicochemical Properties Of Pcsmentioning
confidence: 99%
“…Others works have found that functional groups containing heteroatoms such as O and N are very favourable to improve the capacitance, and these groups can be introduced using different doping methods, as chemical oxidations, plasma treatment, or electrochemical treatments. [18,19,20]. The main aim of oxidation of a carbon surface is obtaining a more hydrophilic surface structure with groups such as carboxyl groups [21,22].…”
Section: Introductionmentioning
confidence: 99%